Positioning digital content on Google Discover: The Case of the Peruvian Newspaper El Comercio - Absi Flores, Luis Miguel; León Ferreyros, Arturo (Estudios sobre el Mensaje Periodístico, 2024)
Media outlets constantly work to reach new audiences and build loyalty through specific strategies. To achieve greater reach, they utilize various platforms, with Google Discover being one of the most popular, used by nearly 1 billion people as of 2018. It is the main source of web traffic acquisition worldwide. The objective of this research is to identify what type of media content is most likely to appear on Google Discover, given its importance as a traffic source. To this end, a quantitative methodology with a descriptive design was employed, based on the content analysis of the 120 most-read news articles between April and September 2023 in the Peruvian newspaper El Comercio. Seven variables (journalistic genre, headline, geolocation, multimedia, topic, length, and source) and 44 categories were established. Among the most notable findings, it was discovered that the news and entertainment genres are the most frequent; government agencies are the primary sources of information for the analyzed content; and finally, medium-length texts (between 11 and 17 lines) clearly performed the best. This case study aims to provide a guide for other media outlets.